A super hydrophobic aluminum alloy and preparation method thereof
By preparing an aluminum alloy with nanopores and modifying its surface with a high-speed airflow impact device, a nano-micron double rough structure is solved, and the problem of complex and high cost of preparing superhydrophobic aluminum alloys in the prior art is achieved, and high efficiency is achieved , environmentally friendly superhydrophobic effects.
Patent Information
- Application Number
- CN202410086815.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-22
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-01-22
AI Technical Summary
The existing superhydrophobic aluminum alloy preparation methods have limitations such as pollution, strict process conditions, special equipment required, time-consuming and expensive raw materials, making it difficult to achieve environmentally friendly, convenient operation, short time-consuming and low-cost industrial applications.
By preparing an aluminum alloy with nanopores and modifying its surface with a high-speed airflow impact device, a nano-micron double rough structure is formed to achieve superhydrophobic effect.
The superhydrophobic aluminum alloy is prepared, with a contact angle between the surface and the water droplets and a rolling angle of less than 10°. It has unique properties such as waterproofing, self-purification, and drag reduction. It has simple process and low cost, which is suitable for industrial applications.
Smart Images

Figure BDA0004675244500000071 
Figure BDA0004675244500000081
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of aluminum alloy materials, and in particular to a super-hydrophobic aluminum alloy and a preparation method thereof. Background Art
[0002] Solid surface super-hydrophobicity (contact angle with water> 150°, rolling angle < 10°) is a common and very special type of interfacial wetting phenomenon, which affects various life activities of animals and plants in nature, such as super-hydrophobic self-cleaning lotus leaves, super-hydrophobic high-load water strider legs, etc. The surface morphology and chemical composition play a key role in the formation of super-hydrophobicity. Aluminum is the largest non-ferrous metal, an important functional and structural material for the development of the national economy, and one of the most widely used and economical materials. The preparation and application of super-hydrophobic aluminum alloys has always been one of the hot spots of research in this field. Existing studies have shown that the surface of super-hydrophobic aluminum alloys has unique properties such as waterproofing, self-cleaning, drag reduction, noise reduction, corrosion resistance, oxidation resistance, and anti-icing, and has extremely huge application potential and broad application prospects. The preparation methods of super-hydrophobic aluminum alloy surfaces mainly include wet chemical etching, oxidation or electrochemical deposition, direct film formation, etc. However, the above methods all have certain limitations, such as pollution, harsh process conditions, special equipment, time-consuming, expensive raw materials, etc. Therefore, exploring preparation methods that are environmentally friendly, easy to operate, short in time, low in cost, and easy to industrialize has important economic and social benefits. Summary of the invention
[0003] Technical problem to be solved: In view of the above technical problems, the purpose of the present invention is to provide a super-hydrophobic aluminum alloy and a preparation method thereof. First, an aluminum alloy with nanopores is prepared to form a nanopore surface rough structure, and then the surface of the nanopore aluminum alloy is modified by a high-speed airflow impact device to form a micron channel. The two are combined to form a nano-micron double rough structure, whose surface contact angle with water droplets is greater than 150°, and the rolling angle is less than 10°, thereby achieving a super-hydrophobic effect.
[0004] Technical solution: A method for preparing a super-hydrophobic aluminum alloy, comprising the following steps:
[0005] S1: Take aluminum alloy substrate powder, add nano-microspheres, and mix them evenly in a mixer;
[0006] S2: Place in a special forming press and press-form at a pressure of 600-700MPa;
[0007] S3: vacuum sintering at 750-800℃ for 1.5-2h, cooling to below 600℃, and extrusion molding;
[0008] S4: washing with running water, drying, and obtaining a nanoporous aluminum alloy;
[0009] S5: The surface of the nanoporous aluminum alloy is modified by a high-speed airflow impact device to obtain a super-hydrophobic aluminum alloy.
[0010] Furthermore, the aluminum alloy substrate powder has a composition of Si 7.41%, Zn 3.15%, Mg 2.87%, Fe 0.87%, and the remainder Al.
[0011] Furthermore, the preparation method of the nanospheres is as follows:
[0012] S11: 90 parts of acrylamide, 0.2 parts of N,N-methylene acrylamide, 0.2-0.4 parts of hectorite and water are mixed to obtain an aqueous dispersion;
[0013] S12: adding the mixture to the itaconic acid solution and stirring evenly to obtain a transparent solution having a total concentration of acrylamide and itaconic acid monomers of 20-50%;
[0014] S13: Take 1 part of Span 60 and 2 parts of Tween 60, add 30 parts of cyclohexane, and stir evenly;
[0015] S14: add the transparent solution of S12 to form a reverse microemulsion, gradually raise the temperature to 45-60°C, then drop ammonium persulfate and sodium bisulfite solution to initiate the reaction, and react for 3-5 hours;
[0016] S15: adding ethanol to break the emulsion and precipitate, washing with acetone for 3-5 times, placing in an oven, and drying at a constant temperature of 60°C for 8 hours;
[0017] S16: After grinding, extract and separate with acetone in a Soxhlet extractor for 8 hours, and dry at a constant temperature of 60°C.
[0018] Furthermore, the modification conditions in S5 are interval modification, with an air flow velocity of 150-200 m / s, an application time of 2-4 min, an interval time of 1 min, and repeated 5-10 times.
[0019] Furthermore, the ratio of acrylamide to itaconic acid is 90:(10-15).
[0020] Furthermore, the neutralization degree of the itaconic acid solution is 55-75%.
[0021] The super-hydrophobic aluminum alloy is prepared by the above-mentioned method for preparing the super-hydrophobic aluminum alloy.
[0022] Beneficial effects:
[0023] 1. The present invention first prepares an aluminum alloy with nanopores to form a nanopore surface roughness structure, and then uses a high-speed airflow impact device to modify the surface of the nanopore aluminum alloy to form a micron channel. The two are combined to form a nano-micron double roughness structure, whose surface contact angle with water droplets is greater than 150° and the rolling angle is less than 10°, achieving a super hydrophobic effect.
[0024] 2. Although nanopores are prepared in the present invention, the mechanical properties are not greatly affected and are basically consistent with those of conventional aluminum alloys. DETAILED DESCRIPTION
[0025] The present invention proposes a super hydrophobic aluminum alloy and a preparation method thereof. In order to make the purpose, technical scheme and effect of the present invention clearer and more specific, the present invention will be further described in detail with reference to the embodiments below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0026] The aluminum alloy substrates in the following examples have the following composition: Si 7.41%, Zn 3.15%, Mg 2.87%, Fe 0.87%, and the balance Al.
[0027] Example 1
[0028] The preparation method of nanoparticles is as follows:
[0029] S11: 90 parts of acrylamide, 0.2 parts of N,N-methylene acrylamide, 0.2 parts of hectorite and water are mixed to obtain an aqueous dispersion;
[0030] S12: adding the mixture to a 60% neutralized itaconic acid solution and stirring evenly to obtain a transparent solution having a total concentration of 20-50% of acrylamide and itaconic acid monomers; the ratio of acrylamide to itaconic acid is 90:13;
[0031] S13: Take 1 part of Span 60 and 2 parts of Tween 60, add 30 parts of cyclohexane, and stir evenly;
[0032] S14: add the transparent solution of S12 to form a reverse microemulsion, gradually raise the temperature to 45°C, then drop ammonium persulfate and sodium bisulfite solution to initiate the reaction, and react for 3 hours;
[0033] S15: Add ethanol to break the emulsion and precipitate, wash with acetone three times, put into an oven, and dry at a constant temperature of 60°C for 8 hours;
[0034] S16: After grinding, extract and separate with acetone in a Soxhlet extractor for 8 hours, and dry at a constant temperature of 60°C.
[0035] Example 2
[0036] The preparation method of nanoparticles is as follows:
[0037] S11: 90 parts of acrylamide, 0.2 parts of N,N-methylene acrylamide, 0.3 parts of hectorite and water are mixed to obtain an aqueous dispersion;
[0038] S12: adding the mixture to a 60% neutralized itaconic acid solution and stirring evenly to obtain a transparent solution having a total concentration of 20-50% of acrylamide and itaconic acid monomers; the ratio of acrylamide to itaconic acid is 90:13;
[0039] S13: Take 1 part of Span 60 and 2 parts of Tween 60, add 30 parts of cyclohexane, and stir evenly;
[0040] S14: add the transparent solution of S12 to form a reverse microemulsion, gradually raise the temperature to 50°C, then drop ammonium persulfate and sodium bisulfite solution to initiate the reaction, and react for 4 hours;
[0041] S15: Add ethanol to break the emulsion and precipitate, wash with acetone 4 times, put into an oven, and dry at a constant temperature of 60°C for 8h;
[0042] S16: After grinding, extract and separate with acetone in a Soxhlet extractor for 8 hours, and dry at a constant temperature of 60°C.
[0043] Example 3
[0044] The preparation method of nanoparticles is as follows:
[0045] S11: 90 parts of acrylamide, 0.2 parts of N,N-methylene acrylamide, 0.4 parts of hectorite and water are mixed to obtain an aqueous dispersion;
[0046] S12: adding the mixture to a 60% neutralized itaconic acid solution and stirring evenly to obtain a transparent solution having a total concentration of 20-50% of acrylamide and itaconic acid monomers; the ratio of acrylamide to itaconic acid is 90:13;
[0047] S13: Take 1 part of Span 60 and 2 parts of Tween 60, add 30 parts of cyclohexane, and stir evenly;
[0048] S14: add the transparent solution of S12 to form a reverse microemulsion, gradually raise the temperature to 55°C, then drop ammonium persulfate and sodium bisulfite solution to initiate the reaction, and react for 4 hours;
[0049] S15: Add ethanol to break the emulsion and precipitate, wash with acetone 4 times, put into an oven, and dry at a constant temperature of 60°C for 8h;
[0050] S16: After grinding, extract and separate with acetone in a Soxhlet extractor for 8 hours, and dry at a constant temperature of 60°C.
[0051] Example 4
[0052] The preparation method of nanoparticles is as follows:
[0053] S11: 90 parts of acrylamide, 0.2 parts of N,N-methylene acrylamide, 0.3 parts of hectorite and water are mixed to obtain an aqueous dispersion;
[0054] S12: adding the mixture to a 60% neutralized itaconic acid solution and stirring evenly to obtain a transparent solution having a total concentration of 20-50% of acrylamide and itaconic acid monomers; the ratio of acrylamide to itaconic acid is 90:10;
[0055] S13: Take 1 part of Span 60 and 2 parts of Tween 60, add 30 parts of cyclohexane, and stir evenly;
[0056] S14: add the transparent solution of S12 to form a reverse microemulsion, gradually raise the temperature to 55°C, then drop ammonium persulfate and sodium bisulfite solution to initiate the reaction, and react for 4 hours;
[0057] S15: Add ethanol to break the emulsion and precipitate, wash with acetone 4 times, put into an oven, and dry at a constant temperature of 60°C for 8h;
[0058] S16: After grinding, extract and separate with acetone in a Soxhlet extractor for 8 hours, and dry at a constant temperature of 60°C.
[0059] Example 5
[0060] The preparation method of nanoparticles is as follows:
[0061] S11: 90 parts of acrylamide, 0.2 parts of N,N-methylene acrylamide, 0.3 parts of hectorite and water are mixed to obtain an aqueous dispersion;
[0062] S12: adding the mixture to a 60% neutralized itaconic acid solution and stirring evenly to obtain a transparent solution having a total concentration of 20-50% of acrylamide and itaconic acid monomers; the ratio of acrylamide to itaconic acid is 90:15;
[0063] S13: Take 1 part of Span 60 and 2 parts of Tween 60, add 30 parts of cyclohexane, and stir evenly;
[0064] S14: add the transparent solution of S12 to form a reverse microemulsion, gradually raise the temperature to 60°C, then drop ammonium persulfate and sodium bisulfite solution to initiate the reaction, and react for 5 hours;
[0065] S15: Add ethanol to break the emulsion and precipitate, wash with acetone 5 times, put into an oven, and dry at a constant temperature of 60°C for 8 hours;
[0066] S16: After grinding, extract and separate with acetone in a Soxhlet extractor for 8 hours, and dry at a constant temperature of 60°C.
[0067] The particle size and gel properties of the nanospheres were tested, and the results are shown in Table 1:
[0068] Table 1
[0069] Particle size (nm) Gel strength (Pa·s) Example 1 20-150 14.11 Example 2 20-150 14.56 Example 3 20-150 14.32 Example 4 15-130 14.49 Example 5 35-200 14.45
[0070] As can be seen from Table 1, the particle size of Example 2 is appropriate and the gel strength is optimal. Therefore, the nanospheres prepared in Example 2 were selected for subsequent experiments.
[0071] Example 6
[0072] A method for preparing a super-hydrophobic aluminum alloy comprises the following steps:
[0073] S1: Take aluminum alloy substrate powder, add the nano-microspheres prepared in Example 2, and place in a mixer to mix evenly;
[0074] S2: Place in a special forming press and press-form at a pressure of 600 MPa;
[0075] S3: vacuum sintering at 750°C for 2h, cooling to below 600°C, and extrusion molding;
[0076] S4: washing with running water, drying, and obtaining a nanoporous aluminum alloy;
[0077] S5: The surface of the nanoporous aluminum alloy was modified by a high-speed airflow impact device. The modification conditions were interval modification, with an airflow velocity of 150 m / s, an application time of 3 min, an interval time of 1 min, and repeated 8 times to obtain a superhydrophobic aluminum alloy.
[0078] Example 7
[0079] A method for preparing a super-hydrophobic aluminum alloy comprises the following steps:
[0080] S1: Take aluminum alloy substrate powder, add the nano-microspheres prepared in Example 2, and place in a mixer to mix evenly;
[0081] S2: Place in a special forming press and press-form at a pressure of 600 MPa;
[0082] S3: vacuum sintering at 750°C for 1.5h, cooling to below 600°C, and extrusion molding;
[0083] S4: washing with running water, drying, and obtaining a nanoporous aluminum alloy;
[0084] S5: The surface of the nanoporous aluminum alloy was modified by a high-speed airflow impact device. The modification conditions were interval modification, with an airflow velocity of 180 m / s, an application time of 3 min, an interval time of 1 min, and repeated 8 times to obtain a superhydrophobic aluminum alloy.
[0085] Example 8
[0086] A method for preparing a super-hydrophobic aluminum alloy comprises the following steps:
[0087] S1: Take aluminum alloy substrate powder, add the nano-microspheres prepared in Example 2, and place in a mixer to mix evenly;
[0088] S2: Placed in a special forming press and pressed at a pressure of 650MPa;
[0089] S3: vacuum sintering at 750°C for 2h, cooling to below 600°C, and extrusion molding;
[0090] S4: washing with running water, drying, and obtaining a nanoporous aluminum alloy;
[0091] S5: The surface of the nanoporous aluminum alloy was modified by a high-speed airflow impact device. The modification conditions were interval modification, with an airflow velocity of 200 m / s, an application time of 3 min, an interval time of 1 min, and repeated 8 times to obtain a superhydrophobic aluminum alloy.
[0092] Example 9
[0093] A method for preparing a super-hydrophobic aluminum alloy comprises the following steps:
[0094] S1: Take aluminum alloy substrate powder, add the nano-microspheres prepared in Example 2, and place in a mixer to mix evenly;
[0095] S2: Placed in a special forming press and pressed at a pressure of 650MPa;
[0096] S3: vacuum sintering at 800°C for 1.5h, cooling to below 600°C, and extrusion molding;
[0097] S4: washing with running water, drying, and obtaining a nanoporous aluminum alloy;
[0098] S5: The surface of the nanoporous aluminum alloy was modified by a high-speed airflow impact device. The modification conditions were interval modification, with an airflow velocity of 180 m / s, an application time of 2 min, an interval time of 1 min, and repeated 8 times to obtain a superhydrophobic aluminum alloy.
[0099] Example 10
[0100] A method for preparing a super-hydrophobic aluminum alloy comprises the following steps:
[0101] S1: Take aluminum alloy substrate powder, add the nano-microspheres prepared in Example 2, and place in a mixer to mix evenly;
[0102] S2: Placed in a special forming press and pressed at a pressure of 650MPa;
[0103] S3: vacuum sintering at 800°C for 1.5h, cooling to below 600°C, and extrusion molding;
[0104] S4: washing with running water, drying, and obtaining a nanoporous aluminum alloy;
[0105] S5: The surface of the nanoporous aluminum alloy was modified by a high-speed airflow impact device. The modification conditions were interval modification, with an airflow velocity of 180 m / s, an application time of 4 min, an interval time of 1 min, and repeated 8 times to obtain a superhydrophobic aluminum alloy.
[0106] Embodiment 11
[0107] A method for preparing a super-hydrophobic aluminum alloy comprises the following steps:
[0108] S1: Take aluminum alloy substrate powder, add the nano-microspheres prepared in Example 2, and place in a mixer to mix evenly;
[0109] S2: Place in a special forming press and press-form at a pressure of 700 MPa;
[0110] S3: vacuum sintering at 800°C for 1.5h, cooling to below 600°C, and extrusion molding;
[0111] S4: washing with running water, drying, and obtaining a nanoporous aluminum alloy;
[0112] S5: The surface of the nanoporous aluminum alloy was modified by a high-speed airflow impact device. The modification conditions were interval modification, with an airflow velocity of 180 m / s, an application time of 3 min, an interval time of 1 min, and repeated 5 times to obtain a superhydrophobic aluminum alloy.
[0113] Example 12
[0114] A method for preparing a super-hydrophobic aluminum alloy comprises the following steps:
[0115] S1: Take aluminum alloy substrate powder, add the nano-microspheres prepared in Example 2, and place in a mixer to mix evenly;
[0116] S2: Place in a special forming press and press-form at a pressure of 700 MPa;
[0117] S3: vacuum sintering at 800°C for 1.5h, cooling to below 600°C, and extrusion molding;
[0118] S4: washing with running water, drying, and obtaining a nanoporous aluminum alloy;
[0119] S5: The surface of the nanoporous aluminum alloy was modified by a high-speed airflow impact device. The modification conditions were interval modification, with an airflow velocity of 200 m / s, an application time of 3 min, an interval time of 1 min, and repeated 10 times to obtain a superhydrophobic aluminum alloy.
[0120] Comparative Example 1
[0121] The difference between this comparative example and Example 7 is that no nano-microspheres are added, specifically:
[0122] A method for preparing an aluminum alloy comprises the following steps:
[0123] S1: Take aluminum alloy substrate powder and mix it evenly in a mixer;
[0124] S2: Place in a special forming press and press-form at a pressure of 600 MPa;
[0125] S3: vacuum sintering at 750°C for 1.5h, cooling to below 600°C, and extrusion molding;
[0126] S4: washing with running water, drying, and obtaining an aluminum alloy;
[0127] S5: The surface of the aluminum alloy is modified by a high-speed airflow impact device. The modification conditions are interval modification, with an airflow velocity of 180 m / s, an application time of 3 min, an interval time of 1 min, and repeated 8 times to obtain the aluminum alloy.
[0128] Comparative Example 2
[0129] The difference between this comparative example and Example 7 is that the high-speed airflow impact device is not used to modify the surface of the nanoporous aluminum alloy, specifically:
[0130] A method for preparing an aluminum alloy comprises the following steps:
[0131] S1: Take aluminum alloy substrate powder, add the nano-microspheres prepared in Example 2, and place in a mixer to mix evenly;
[0132] S2: Place in a special forming press and press-form at a pressure of 600 MPa;
[0133] S3: vacuum sintering at 750°C for 1.5h, cooling to below 600°C, and extrusion molding;
[0134] S4: Rinse with running water, dry, and obtain nanoporous aluminum alloy.
[0135] The static contact angle of 5 μL deionized water on the sample surface was measured by a dynamic contact angle detection system, and the rolling angle was measured using an adjustable tilt angle platform.
[0136] Table 2
[0137] Contact angle (°) Roll angle (°) Example 6 158.7 5.6 Example 7 164.2 4.8 Example 8 165.1 4.7 Example 9 160.6 5.0 Example 10 162.5 5.0 Embodiment 11 157.5 5.8 Example 12 164.3 4.8 Comparative Example 1 121.4 9.1 Comparative Example 2 103.9 8.5
[0138] The mechanical properties of each embodiment were tested using a universal testing machine.
[0139] Table 3
[0140]
[0141]
Claims
1. A method for preparing a super-hydrophobic aluminum alloy, characterized in that: The following steps are involved: S1: Take aluminum alloy substrate powder, add nano-microspheres, and mix them evenly in a mixer; S2: Place in a special forming press and press-form at a pressure of 600-700MPa; S3: vacuum sintering at 750-800℃ for 1.5-2h, cooling to below 600℃, and extrusion molding; S4: washing with running water, drying, and obtaining a nanoporous aluminum alloy; S5: The surface of the nanoporous aluminum alloy is modified by a high-speed airflow impact device to obtain a super-hydrophobic aluminum alloy; The preparation method of the nanospheres is as follows: S11: 90 parts of acrylamide, 0.2 parts of N,N-methylene acrylamide and 0.2-0.4 parts of hectorite are mixed with water to obtain an aqueous dispersion; S12: adding the mixture to the itaconic acid solution and stirring evenly to obtain a transparent solution having a total concentration of acrylamide and itaconic acid monomers of 20-50%; S13: Take 1 part of Span 60 and 2 parts of Tween 60, add 30 parts of cyclohexane, and stir evenly; S14: add the transparent solution of S12 to form a reverse microemulsion, gradually raise the temperature to 45-60°C, then drop ammonium persulfate and sodium bisulfite solution to initiate the reaction, and react for 3-5 hours; S15: adding ethanol to break the emulsion and precipitate, washing with acetone for 3-5 times, placing in an oven, and drying at a constant temperature of 60°C for 8 hours; S16: After grinding, extract and separate with acetone in a Soxhlet extractor for 8 hours, and dry at a constant temperature of 60°C.
2. A method for preparing a super hydrophobic aluminum alloy according to claim 1, characterized in that, The aluminum alloy substrate powder has a composition of Si 7.41%, Zn 3.15%, Mg 2.87%, Fe 0.87%, and the balance Al.
3. A method for preparing a super hydrophobic aluminum alloy according to claim 1, characterized in that, The modification conditions in S5 are intermittent modification, with an air flow velocity of 150-200 m / s, an application time of 2-4 min, an interval time of 1 min, and repeated 5-10 times.
4. A method for preparing a super hydrophobic aluminum alloy according to claim 1, characterized in that, The ratio of acrylamide to itaconic acid is 90:(10-15).
5. A method for preparing a super hydrophobic aluminum alloy according to claim 1, characterized in that, The neutralization degree of the itaconic acid solution is 55-75%.
6. A super-hydrophobic aluminum alloy prepared according to the preparation method of the super-hydrophobic aluminum alloy according to any one of claims 1 to 5.
Citation Information
Patent Citations
High-strength hydrophobic aluminum alloy material and preparation method thereof
CN115595479A